Analytical Stress-Strain Model for FRP-Confined Rectangular RC Columns - Megalooikonomou, Konstantinos G.; Papavasileiou, Georgios S. (Frontiers in Built Environment, 2019)
One of the major applications of Fiber Reinforced Polymers (FRPs) in construction is in the confinement of reinforced concrete (RC) columns. The performance of FRP-confined concrete in circular columns has been extensively investigated in literature and the efficiency of the available models is nowadays considered to be satisfactory. However, the case of confinement of rectangular RC sections with FRPs is a more complex problem, the mechanism of which has not yet been adequately described. The aim of this work is to simplify the problem by proposing an iterative procedure based on the results of a three-dimensional finite element (3D FEM) analysis. An interesting finding is that the arching effect is not observed: indeed, the unconfined regions are partially confined and contribute a certain amount to the overall strength of the rectangular RC sections. Based on (a) a system of ‘generalized’ springs, (b) well-known stress-strain laws and (c) a failure criterion, a simplified mechanical model which gives the stress-strain behaviour of a rectangular RC section confined by FRPs under concentric load is proposed. The algorithm takes into account all parameters available to designers, such as corner rounding radius, stiffness of the FRP and concrete strength, while it can be easily understood and implemented. Its results are found to correlate adequately to recent experimental data yielded by large-scale tests on FRP-confined rectangular RC columns. Finally, in order to further evaluate the performance of this material model, it was implemented in the simulation of a series of experimental tests of FRP-retrofitted square RC columns under cyclic lateral loading simulating earthquake loads and simultaneous constant axial compression. In particular, all specimens were simulated using nonlinear fiber elements, in which the FRP-confined concrete was modelled using the aforementioned material model. Comparison between the numerical and experimental hysteresis of the column is indicative of the effectiveness of the implemented modelling.